RuO2 center dot nH(2)O nanoparticles anchored on carbon nano-onions: an efficient electrode for solid state flexible electrochemical supercapacitor - Muniraj, Vedi Kuyil Azhagan; Kamaja, Chaitanya Krishna; Shelke, Manjusha V. (ACS Sustainable Chemistry & Engineering, 2016)
A flexible solid state electrochemical capacitor based on hydrous RuO2 nanoparticles, supported onto the nonporous and highly accessible ion adsorptive carbon nano onions (CNOs), is fabricated in a novel process of modifying a conducting carbon paper to a flexible conducting substrate, separated with a poly(vinyl alcohol)/H2SO4 gel electrolyte. The sol-gel technique tends to form homogeneously dispersed RuO2 nanoparticles with the average size of similar to 2.3 nm on the positive surface curvatures of multilayer fullerene (CNOs), which helps the high diffusivity of ions in both the aqueous and solid state gel electrolytes. The flexible substrate worked excellently as an electrical conductor as well as a stable mechanical support. This solid state flexible energy storage device showed a maximum energy density of 10.62 Whkg(-1) and a maximum power density of 4.456 kWkg(-1) for the hydrous RuO2/CNOs nanocomposite with 94.47% cycling stability even after 4000 cycles.
Keywords: Carbon nano-onions; Electrochemical capacitor; Flexible conducting substrate; Flexible energy storage device; Hydrous ruthenium oxide nanoparticles

Ni(OH)(2)-Fe2O3/CNOs ternary nanocomposite designed as an anode with complementary properties for high-performance li-ion battery - Dwivedi, Pravin Kumari; Muniraj, Vedi Kuyil Azhagan; Devarapalli, Rami Reddy; Shelke, Manjusha V. (Chemistryselect, 2018)
Synthesis of the new ternary hybrid composite with excellent electrochemical performances for Li-ion battery is demonstrated. The ternary hybrid composite of Ni(OH)(2)-Fe2O3/Carbon Nano Onions (NFOC) is synthesized by using two-step solution phase method delivers a high reversible discharge capacity of 928 mAhg(-1) at 50 mAg(-1) and 673 mAhg(-1) at a higher current density of 1000 mAg(-1) with excellent rate performance. Additionally, it shows to have stable cycle life up to 1000 cycles with 96% capacity retention and more than 99% of coulombic efficiency. The synergetic effect between Ni(OH)(2), Fe2O3 and carbon nano onions (CNOs) as well as the unique feature of heterostructures are responsible for the improved electrochemical performance of the battery. The reversible reaction of Fe2O3 and Ni(OH)(2) with Li, maintains its long cycle life with higher reversible discharge capacity and CNOs improve the efficient electronic transfer, accommodate substantial volume expansion and maintain the structural integrity of the material during lithiation-delithiation process.
Keywords: Heterostructures; Long cycle stability; Superior rate capability; Ternary Composite; Transition metal oxides

High-energy flexible supercapacitor-synergistic effects of polyhydroquinone and RuO2 center dot xH(2)O with microsized, few-layered, self-supportive exfoliated-graphite sheets - Muniraj, Vedi Kuyil Azhagan; Dwivedi, Pravin Kumari; Tamhane, Parikshit Shivaji; Szunerits, Sabine; Boukherroub, Rabah; Shelke, Manjusha Vilas (ACS Applied Materials & Interfaces, 2019)
An effective and straightforward route for tailoring the self-supporting, exfoliated flexible graphite substrate (E-FGS) using electrochemical anodization is proposed. E-FGS has essential features of highly exfoliated, few-layered, two-dimensional graphite sheets with the size of several tens of micrometers, interconnected along the axis of the substrate surface. The novel hierarchical porous structural morphology of E-FGS enables large active sites for efficient electrolyte ion and charge transport when used as electrode material for a supercapacitor. In order to effectively utilize this promising E-FGS electrode for energy storage purpose, a ternary composite is further synthesized with pseudocapacitive polyhydroquinone (PHQ) and hydrous RuO2 (hRO). hRO is synthesized via a sol-gel route, while electropolymerization is utilized for the electrodeposition of PHQ over E-FGS. Ultimately, the fabricated self-supporting E-FGS-based flexible supercapacitor is capable of delivering areal specific capacitance values as high as 378 mF cm(-2) at a current density of 1 mA cm(-2). Addition of the pseudocapacitive component to the E-FGS texture leads to similar to 10 times increase of the electrochemical charge storage capability. The imposition of mechanical forces to this flexible supercapacitor device results in trivial changes in electrochemical properties and is still capable of retaining 91% of the initial specific capacitance after 10 000 cycles. Alongside, the fabricated symmetrical solid-state flexible device exhibited a high energy density of 8.4 mu Wh cm(-2). The excellent performance along with the ease of synthesis and fabrication process of the flexible solid-state supercapacitor device using PHQ/hRO/E-FGS holds promise for large-scale production.
Keywords: graphite exfoliation; polyhydroquinone; ruthenium oxide; solid-state flexible supercapacitor; Ternary Composite

Flexible energy storage device based on poly(N-phenylglycine), an incentive-energy pseudocapacitive conducting polymer, and electrochemically exfoliated graphite sheets - Muniraj, Vedi Kuyil Azhagan; Boukherroub, Rabah; Shelke, Manjusha Vilas (ACS Sustainable Chemistry & Engineering, 2020)
Poly(N-phenylglycine) (PNPG), an original pseudocapacitive conjugative conducting polymer (CP), was synthesized by the electro-oxidative polymerization method. The synthesis process involves in situ polymerization and electro-deposition of N-phenylglycine onto the surface of highly conductive, few-layered, exfoliated flexible graphite sheets (EFGSs). At first, the promising features of the conjugative structure of the as-prepared protonated PNPG were thoroughly investigated by UV-vis absorption spectrophotometry, micro-Raman spectroscopy, and X-ray photoelectron spectroscopy analysis. The protonated nitrogen groups facilitate the rapid accessibility of counter ions from the electrolyte. Electrochemical studies revealed that the PNPG/E-FGS electrode exhibits an extraordinary areal specific capacitance of 367 mF cm(-2) at 10 mV s(-1). A flexible solid-state symmetrical supercapacitor was further fabricated using PNPG/E-FGS electrodes, exhibiting a specific capacitance as high as 199 mF cm(-2) at 1 mA cm(-2) with an operating voltage of 1.1 V. Furthermore, the device delivered an excellent specific energy of 8.36 mu W h cm(-2) at a power density of 1.65 mW cm(-2) in a working potential window of 1.1 V. More significantly, the energy density was nearly doubled to 16.1 mu W h cm(-2) upon extending the potential window from 1.1 to 1.5 V. The extremely redox-active CP electrode is highly suitable for applications in high-energy electrochemical capacitors with wide operating potential window.
Keywords: conducting polymer; electro-polymerization; exfoliated graphite; flexible supercapacitor; poly(N-phenylglycine)